Anti-corruption education as a means of corruption counteraction: notion and content - P. A. Kabanov (Russian Journal of Economics and Law, 2014)
Objective: to elaborate and propose the theoretically grounded definition of anti-corruption education as a legal category. Methods: dialectic method of cognition. Results: The article presents structural analysis of legal and scientific definitions of anti-corruption education, formulated in the regional legislation of the Russian Federation, as well as in the scientific and reference literature; the objects and subjects of anti-corruption education are defined, as well as means of information anti-corruption impact. Scientific novelty: Basing on the research, the new variant of the scientific and legal category “legal education” is proposed. It significantly differs from the previous definitions and discloses its content. Practical value: The elaborated scientific category of anti-corruption education allows to disclose the content of this activity and may promote further research.